Poor Adherence With Medication Refill and Medical Supplies Maintenance as Risk Factors for Inpatient Asthma Admission in Children - Poowuttikul, Pavadee (Glob Pediatr Health, 2017)
Background. Asthma results in significant pediatric hospitalizations in the inner city. Many asthmatic children were admitted to our hospital as a result of lack of medications or medical supplies that had been previously prescribed (“ran out,” “broken,” or “lost”). Objective. To identify the incidence of children admitted for asthma because of lack of prescribed medications/supplies and to assess risk factors for poor adherence between groups. Methods. This was a prospective chart review of 200 asthmatic children admitted to Children’s Hospital of Michigan, Detroit. The data included asthma severity, lack of prescribed medications/medical supplies, and outpatient management. Results. In all, 35.5% or 71/200 of asthmatic children admitted had lack of prescribed medication/supplies (9% lacked both). The most common deficiency was β2-agonist (20.5%; 41/200). Teenagers had the highest lack of medications/medical supplies (55.6%; 5/9) compared with toddlers (17.2%; 16/93) and preschoolers (17.9%; 5/28). Patients with severe persistent asthma had a higher incidence of lacking medicine (31.8%; 7/22) compared with 25% (14/56) with moderate persistent asthma and 23.4% (15/64) of mild asthmatics. We found the lack of asthma medical supplies, including nonfunctioning or lost nebulizers/spacers, in 44.4% (4/9) of teenagers, 17.2% (16/93) of toddlers, and 21.4% (6/28) of preschool-aged children. We found no significant difference in these deficiencies whether patients were managed by asthma specialists or primary care providers. Conclusions. Significant numbers of asthmatic children admitted reported lack of prescribed medications/medical supplies. The most severe asthmatics were most likely to run out of medications. Interventions targeted at these deficiencies may avoid hospitalizations.